Real time estimation of slant path tropospheric delay at very low elevation based on singular ground‐based global positioning system station. Issue 7 (1st August 2013) - Zhu, Qinglin; Zhao, Zhenwei; Lin, Leke
Abstract : Real time slant path tropospheric delay (STD) is of benefit in near real‐time weather forecasting, climatologic applications, and reconstructing refractivity profile. For low elevation ( < 5°), the traditional method precision of calculating STD is poor. A new method of estimating real‐time STD at very low elevation (0° − 5°), which is based on singular ground‐based Global Positioning System (GPS) with International GPS Service ultra‐rapid product, is presented in this study. An experiment was carried out to validate the feasibility on an island in Shantou, south China during July 2009. Results from radiosondes, GPS and models are compared and show that GPS‐derived results have agreement with those from radiosonde for low elevation ( < 5°). Consequently, the method can potentially offset some drawbacks of traditional method, and even may be used for monitoring the troposphere without radiosondes in some aspects in the future.